A Comparative Analysis of the Roles Governors Play in Disaster Recovery. Issue 2 (17th January 2018) - Smith, Gavin; Sabbag, Lea; Rohmer, Ashton
Abstract: This article examines the roles that governors play in disaster recovery, a topic that remains underemphasized in both the research and practice‐based literature. In order to more fully explore these roles, we interviewed former Governors James B. Hunt, Jr. (D‐NC) and Haley Barbour, (R‐MS), who were in office following Hurricanes Floyd (1999) and Katrina (2005) respectively—two events that represent the costliest disasters in the history of both states. Interview questions were framed across three dimensions of disaster recovery: The rules governing disaster assistance and the degree to which associated programs and policies address local needs, the timing of disaster assistance, and the level of horizontal and vertical integration across organizations that deliver disaster assistance. Additional questions focused on gubernatorial leadership and planning for recovery. Based on the findings, we posit a number of policy recommendations, next steps, and future areas of study.